Thermal Remote Sensing for Water Outflows Detection and Determination of the Role of Lineaments in Underground Hydrodynamics of Evia Island, Central Greece - Athanasiadou, Laoura; Psomiadis, Emmanouil; Stamatis, Georgios (Bulletin of the Geological Society of Greece, 2020)
The coastal karst system of Evia Island is developed due to the extended presence of carbonate formations, discharges into the sea either at the coastal zone or via submarine springs, having a direct relation to the tectonic system of the area. Thermal infrared remote sensing has been proved its capability in monitoring thermal differentiations of coastal water plumes. This work aims to locate the freshwater outflows through remote sensing and specific with the use of Landsat’s 8 thermal images and to reveal how the lineaments of the area control this karstification process. L8 contains two thermal bands (Band 10, high gain and Band 11, low gain) with resolution 30m which record the scattering of infrared radiation from the sea surface. Spectral Band 10 was selected due to the high gain characteristics which provide more suitable radiometric resolution (sensitivity). Finally, combing thermal images with geological maps, sea surface temperature (SST) maps have been created.